The Influence of Human Resources Quality and Supporting Facilities on the Quality of Health Services (A Study of PT Hasnur Riung Sinergi's COVID-19 Positive Employee Management Vendors Throughout South Kalimantan) - Adhitya Chandra Setyawan; Sulastini Sulastini; Mohammad Zainul (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study is to examine and analyze the influence of the quality of human resources (HR) in healthcare and supporting infrastructure on the quality of healthcare services provided by healthcare vendors to employees of PT. Hasnur Riung Sinergi in South Kalimantan, particularly during the COVID-19 response. This research is expected to provide an overview of the factors that determine the quality of healthcare services within the company. The research method used was a quantitative approach with an explanatory research design. The study sample consisted of 95 respondents, patients or employees of PT. Hasnur Riung Sinergi at the AGM Block 3 site in Hulu Sungai Selatan Regency and the AGM Block 4 site in Tapin Regency who had previously tested positive for Covid-19 and received services from a healthcare vendor. Data were collected through a questionnaire and analyzed using multiple linear regression techniques with the help of SPSS version 25. The results of the study show that the quality of health human resources and supporting infrastructure have a significant influence on the quality of health services, both partially and simultaneously. The conclusion of this study is that improving the competence of health human resources and the completeness of supporting infrastructure are key factors in improving the quality of vendor health services, thus having a direct impact on patient satisfaction and safety.